CASE SERIES OF NEONATAL DIABETES WITH KCNJ11 MUTATION_ TRANSFER FROM INSULIN TO SULPHONYLUREA - Teoh, Sze Teik; Wong, Jeanne Sze Lyn; Selveindran, Nalini M; Amin, Noor Arliena Mat; Leong, Annie; Tee, Pian Pian; Cheng, Hooi Peng; Gan, Cheng Guang; Anand, L Alexis; Ch'ng, Tong Wooi; Ibrahim, Mastura; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Permanent neonatal diabetes, presenting before 6 months old, signifies a monogenic cause. Mostly, it involves mutation of KCNJ11 gene that encodes the Kir6.2 subunit of the ATP-sensitive potassium channel (KATP). The landmark findings by Gloyn et al (NEJM 2004) on oral sulphonylurea (SU) binding to KATP and closing it by a non-ATP dependent route has markedly changed the landscape of management. METHODOLOGY Cross-sectional review of medical records. RESULTS 3 patients (A, B, C) included. (A) presented at day 14, while (B&C) both at 2-month-old. (A) had hyperglycemia without ketosis while (B&C) had severe DKA. (B) also had seizures with delayed motor development (possibly intermediate DEND). All were initiated with subcutaneous insulin at diagnosis. Genetic tests were performed at 8-year-old, 1-year-old, and 5-month-old, respectively. Both (B&C) were similarly heterozygous for a pathogenic KCNJ11 missense variant with p.(Arg201Cys). Transfer to SU was performed based on the published protocol by Prof Andrew Hattersley from the University of Exeter. Time to SU varied with the slowest transfer at 8-year-9-month-old and quickest at 1-year-7-month-old. All transfers were successful with insulin weaned off. Noticeable improvement of HbA1c and C-peptide were demonstrated after 12 weeks. HbA1c decreased from 8% to 5.7%, 8.9% to 6.2%, and 9.6% to 5.8%; C-peptide improved from undetected (<33 pmol/L) to 185 pmol/L, 861 pmol/L, 73 pmol/L, respectively. (B) showed minimal response initially to gliclazide but an excellent response to glibenclamide. Initial glibenclamide dose varied from 0.8 mg/kg/day to 1.6 mg/kg/day. No hypoglycemia or GI complications. (A) needed to restart insulin at 13-year-8-month-old, 5 years after the transfer. (A) was the last to transfer to SU and required a higher initial dose. CONCLUSION Neonatal diabetes warrants rapid and focused genetic analysis to identify the genotypes with modifiable outcomes. Early genetic confirmation facilitates the transfer to oral SU for better glycaemic and neurodevelopmental outcomes and potentially improves the durability of the treatment.